Capacity Decisions with Demand Fluctuations and Carbon Leakage - Guy Meunier; Jean-Pierre Ponssard (Center for Economic Studies and ifo Institute (CESifo), 2014)
For carbon-intensive, internationally-traded industrial goods, a unilateral increase in the domestic CO2 price may result in the reduction of the domestic production but an increase of imports. In such sectors as electricity, cement or steel, the trade flows result more from short-term regional disequilibria between supply and demand than from international competition. This paper formalizes this empirical observation and characterizes its impact on leakage. Domestic firms invest in home plants under uncertainty; then, as uncertainty unfolds, they may source the home market from their home plants or from imports. We prove that there would be no leakage in the short-term (without capacity adaptation) but there would be in the long-term (with capacity adaption). Furthermore, the larger the uncertainty the larger the leakage is. We also characterize the impacts of uncertainty on the (short-term and long-term) pass-through rates. In the concluding section we discuss the implications of these results for the evaluation of climate policies.
Keywords: D81; D92; Q56; L13; 330; carbon leakage; demand fluctuations; capacity decisions